Increased SBA-15-SO3H Catalytic Activity through Hydrophilic/Hydrophobic Fluoroalkyl-Chained Alcohols (RFOH/SBA-15–Pr-SO3H) - Rostamnia, Sadegh; Doustkhah, Esmail (Synlett, 2015)
A superior catalytic activity for the SBA-15-functionalized sulfonic acid containing fluoroalkyl chain alcohols (RFOH/SBA-15–Pr-SO3H adduct) is presented for the synthesis of highly substituted imidazoles. The advantages of this method include low catalyst loading, simple procedure, excellent yields, recyclability of catalyst, and short reaction times.
Keywords: fluoroalkyl chain alcohols; TFE/SBA-15–Pr-SO3H; imidazole; multicomponent reaction